TAHFIZH AL-QUR'AN LEARNING MODEL AT THE ABDULLAH WA SALMA SUMBAWA ISLAMIC BOARDING SCHOOL - Abdul Hakim; Khozin; Ishomuddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study focuses on the structure of the Qur'anic tahfizh learning model, as well as the factors that facilitate and hinder its implementation. The research was carried out through a qualitative approach with a case study at the Abdullah Wa Salma Islamic Boarding School in Sumbawa. Data collection was carried out by means of in-depth interviews, direct observation involving researchers, and document studies. The collected data was then analyzed using interactive analysis techniques from Miles and Huberman. The results of the study revealed that the learning model applied was a combined modification that systematically combined the methods of halaqah, takrir, simā’i, and independent murāja’ah. The success of this model is supported by the positive role of the ustadz as an example and the existence of a structured coaching system. However, there are obstacles in the form of differences in motivation between students and lack of time to do murāja’ah together. This study concludes that the adaptive tahfizh learning model has proven to be relevant and effective in producing qualified Qur'an memorizers, as well as making contributions both theoretically through the synthesis of adaptive tahfizh learning models and practically.